Research Progress for RNA Modifications in Physiological and Pathological Angiogenesis - Chen, Hui-Ming; Li, Hang; Lin, Meng-Xian; Fan, Wei-Jie; Zhang, Yi; Lin, Yan-Ting; Wu, Shu-Xiang (Frontiers in Genetics, 2022)
As a critical layer of epigenetics, RNA modifications have a variety of molecular functions and participate in numerous biological processes. RNA modifications have been shown to be essential for embryogenesis and stem cell fate. As high-throughput sequencing and antibody technologies have advanced by leaps and bounds, the association of RNA modifications with multiple human diseases have sparked research enthusiasm; additionally, aberrant RNA modification leads to tumor angiogenesis by regulating angiogenesis-related factors. This review collected recent cutting-edge studies focus on RNA modifications (N6-methyladenosine (m6A), N5-methylcytosine (m5C), N7-methylguanosine (m7G), N1-methyladenosine (m1A), and pseudopuridine (Ψ)), and their related regulators in tumor angiogenesis. to emphasize the role and impact of RNA modifications.